The Essex Serpent - Perry, Sarah, 1979- (Serpent's Tail, 2016)
Set in Victorian London and an Essex village in the 1890's, and enlivened by the debates on scientific and medical discovery which defined the era, The Essex Serpent has at its heart the story of two extraordinary people who fall for each other, but not in the usual way. They are Cora Seaborne and Will Ransome. Cora is a well-to-do London widow who moves to the Essex parish of Aldwinter, and Will is the local vicar. They meet as their village is engulfed by rumours that the mythical Essex Serpent, once said to roam the marshes claiming human lives, has returned. Cora, a keen amateur naturalist is enthralled, convinced the beast may be a real undiscovered species. But Will sees his parishioners' agitation as a moral panic, a deviation from true faith. Although they can agree on absolutely nothing, as the seasons turn around them in this quiet corner of England, they find themselves inexorably drawn together and torn apart. Told with exquisite grace and intelligence, this novel is most of all a celebration of love, and the many different guises it can take.